2004
DOI: 10.1073/pnas.0407020102
|View full text |Cite
|
Sign up to set email alerts
|

On the capturing of low-energy electrons by DNA

Abstract: Many of the mutagenic or lethal effects of ionization radiation can be attributed to damage caused to the DNA by low-energy electrons. To gain insight on the parameters affecting this process, we measured the low-energy electron (<2 eV) transmission yield through self-assembled monolayers of short DNA oligomers. The electrons that are not transmitted are captured by the layer. Hence, the transmission reflects the capturing efficiency of the electrons by the layer. The dependence of the capturing probability on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
162
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(171 citation statements)
references
References 33 publications
7
162
1
1
Order By: Relevance
“…[37] However, experiments on the electron-capturing efficiencies of short DNA oligomers provide the only estimate of the relative order of the vertical electron attachment energies (VEAs) for DNA single strands. [4] Theoretical investigations at various levels of sophistication have been complemented with experimental explorations. The coupled cluster level of theory with single, double, and perturbative triple excitations (CCSD(T)) successfully elucidated the tautomeric forms of the covalent bond radical anion of guanine [33,38] and adenine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] However, experiments on the electron-capturing efficiencies of short DNA oligomers provide the only estimate of the relative order of the vertical electron attachment energies (VEAs) for DNA single strands. [4] Theoretical investigations at various levels of sophistication have been complemented with experimental explorations. The coupled cluster level of theory with single, double, and perturbative triple excitations (CCSD(T)) successfully elucidated the tautomeric forms of the covalent bond radical anion of guanine [33,38] and adenine.…”
Section: Introductionmentioning
confidence: 99%
“…Electron attachment to DNA fragments is one of the most attractive subjects in both radiation biology [1][2][3][4] and functional nanomaterial science. [5][6][7][8] Knowledge of the distribution of excess electron sites for DNA strands is crucial for understanding important biochemical processes, such as anion-related DNA damage and repair, [1,[9][10][11][12][13][14][15][16][17] charge transfer, [5][6][7][18][19][20][21][22][23] and mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Ray et al showed experimentally that LEEs are ready to attach to the short single-stranded guanine-rich oligomers. [15] Sanche's group observed significant contributions of guanine in LEE-induced DNA single-strand breaking. [14] Using a reliably high level of theory, Schaefer et al predicted the substantial electron capturing ability of the 2'-deoxyguanosine-3',5'-diphosphate in both gas-phase and aqueous solutions.…”
mentioning
confidence: 98%
“…[6,21] However, the most straightforward mechanism of electroninduced strand breakage would be a direct attachment to the backbone followed by a C À O or P À O bond cleavage. Recent high-resolution electron energy loss spectroscopy (HREELS) measurements on DNA suggested that low-energy electrons mainly interact with the DNA backbone.…”
mentioning
confidence: 99%